Qualidade microbiológica, físico-química e parasitológica do queijo mussarela fatiado - Silva, Leônia Régia Costa da (Universidade Federal Rural do Semi-Árido, 2021)
The objective was to evaluate the microbiological, physicochemical and parasitological quality of sliced mozzarella cheese and the microbiological quality and its packaging. For this purpose, samples of sliced mozzarella cheese were collected from commercial establishments in the municipality of Mossoró in the state of Rio Grande do Norte. Ten samples were collected in establishments that were randomly selected. For analysis, the samples and their packaging underwent microbiological analysis of total and thermotolerant coliforms, counting of mesophilic aerobic bacteria, molds and yeasts, and research on Salmonella spp., as well as physical-chemical analyzes of pH, moisture, acidity, color and marketing temperature and parasitological analysis. All cheese and packaging samples 100% (10/10) were in accordance with current legislation standards for the analysis of total and thermotolerant coliforms and negative results were identified for the analysis of Salmonella spp. The results of mold and yeast counts varied between 6.62 to 8.48 log10 CFU/g for cheese and 1.11 to 2.78 log10 CFU/g for packaging, where the ideal would be the absence of these microorganisms. In the same way, in the counting of mesophilic bacteria, it was observed fluctuations from 5.95 to 8.73 log10UFC/g for cheese and 2.17 to 2.96 log10UFC/g for packaging. The mean equivalent to the pH varied between 4.19 and 5.45, where 60% (6/10) of the samples are outside the recommended range. In the acidity analysis, a variation of 0.11 to 0.18% was observed. The commercialization temperature ranged between 4.4 and 19.4 ºC, with the temperature of 4/10 of the samples analyzed being incompatible with what is required by law. Humidity ranged between 40.39 and 48.32%, classifying 90% (9/10) as medium humidity and 10% (1/10) as high humidity. In the color analysis in the L* parameter, values close to 100 were obtained, showing a trend towards lighter colors, in the a* parameter it was observed that 20% (2/10) of the samples had negative values indicating a tendency to green, and 80% (8/10) presented their positive values showing a tendency to red, in parameter b* 100% (10/10) of the samples had a tendency to yellow. In the parasitological analysis, 90% (9/10) of the samples had no parasitological agents, while 10% (1/10) had a positive result, and the parasitological agent found in this sample was Toxocara sp. Based on the data, it appears that greater attention is needed to the quality of the food analyzed, considering the microbial contamination, physicochemical standards outside the requirements, and thus offering risks to the health of consumers causing risk to the health of their consumers, in addition to the need to adopt measures to ensure a quality product
Keywords: Análise de alimento; Derivado lácteo; Microrganismos indicadores; Segurança Alimentar; Food analysis; Dairy derivative; Indicating microorganisms; Food security; CIENCIAS AGRARIAS::ZOOTECNIA